Seasonal Distribution, Antimicrobial Activity, and Risk Factors Associated with the Incidence of Staphylococcus Species in Bovine Milk from a Dairy Farm in Eastern Cape, South Africa - Monday, Idamokoro Emrobowansan; Hosu, Yiseyon Sunday (Asian Journal of Agriculture and Rural Development, 2022)
The present study aimed to evaluate the incidence and seasonal distribution of Staphylococcus species on a medium-scale dairy farm and investigate their antimicrobial sensitivity with selected standard antibiotics. Several biochemical tests with the API staph kits were utilized to recognize the presence of micro-bacteria in the milk a species level. The antimicrobial activity was evaluated following the approved Clinical Laboratory Standard Institute (CLSI) guidelines. In total, 217 samples of milk were cultured for bacterial tests over nine months. Of the 217 milk samples analyzed, 13 varied Staphylococcus species were identified from the 86 (39.63%) positive isolates. Of the identified isolates, Staphylococcus xylosus (22.09%), Staphylococcus hominis (15.11%), and Staphylococcus haemolyticus (11.63%) were the most common. Bacteria species that showed resistance to the 15 different antimicrobial agents used in this study included Staphylococcus xylosus (80%), Staphylococcus sciuri (60%), Staphylococcus aureus (53.33%), Staphylococcus haemolyticus (46.67%), Staphylococcus epidermidis (46.67%), and Staphylococcus chromogenes (40%). The results found a high incident rate and multiple Staphylococcus species resistant to antimicrobial drugs like penicillin and ampicillin, which are utilized on the farm, which calls for drastic measures.